2011
DOI: 10.1345/aph.1p586
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Alternaria Keratitis with Intrastromal and Topical Caspofungin in Combination with Intrastromal, Topical, and Oral Voriconazole

Abstract: Intrastromal and topical caspofungin were employed in combination with voriconazole for the management of refractory Alternaria keratitis, with no observed adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 7 publications
(8 reference statements)
0
23
0
Order By: Relevance
“…However, the body of clinical evidence for its use is not strong, and consists mainly of single case reports48–50 and small, or uncontrolled interventional case series 51–55. Other agents, namely caspofungin and amphotericin have also been reported for intrastromal use, but again only in case report format 56 57 Table 3. summarises published studies of intrastromal antifungals for fungal keratitis.…”
Section: Intrastromal Antimicrobialsmentioning
confidence: 99%
“…However, the body of clinical evidence for its use is not strong, and consists mainly of single case reports48–50 and small, or uncontrolled interventional case series 51–55. Other agents, namely caspofungin and amphotericin have also been reported for intrastromal use, but again only in case report format 56 57 Table 3. summarises published studies of intrastromal antifungals for fungal keratitis.…”
Section: Intrastromal Antimicrobialsmentioning
confidence: 99%
“…Over the last few years, a few cases of Alternaria keratitis treated with a combination of topical and intrastromal/intracameral antifungals have been reported. [2][3][4][5] Voricanozole was first reported for the management of Alternaria keratitis by Ozbek et al 2 with resolution of the infection within 10 days of beginning therapy. Tu 4 reported three cases of Alternaria keratitis that responded rapidly to either topical fluconazole 0.02% or a combination of intrastromal voriconazole and topical caspofungin 0.5%.…”
mentioning
confidence: 99%
“…Tu 4 reported three cases of Alternaria keratitis that responded rapidly to either topical fluconazole 0.02% or a combination of intrastromal voriconazole and topical caspofungin 0.5%. Neoh et al 5 reported a case of Alternaria keratitis in a patient with a corneal graft that was successfully managed with intrastromal and topical caspofungin in combination with intrastromal, topical, and oral voriconazole. However, once the infection was under control, the patient underwent penetrating keratoplasty.…”
mentioning
confidence: 99%
“…After topical delivery in animals, caspofungin has good penetration into eyes with inflammation or corneal abrasion (4,20), and it has been shown previously to be effective in treating fungal keratitis in rabbits (5,12). While penetration into intact human eyes may be limited (10), successful application of topical caspofungin alone (7) or in combination with voriconazole (11,18) for patients with fungal keratitis has been reported. However, the stability of extemporaneously prepared caspofungin eye drops is unknown and the eye drops have to be freshly prepared and used within 24 h (7), making their use in clinical settings uneconomical.…”
mentioning
confidence: 99%
“…By following an intensive regime of one drop (0.05 ml) administered every 1 or 2 h in clinical practice (11,18), a total of 0.6 to 1.2 ml of eye drops would be applied daily. A single 50-mg caspofungin vial provides two 5-ml bottles of eye drops, each sufficient for 4 to 8 days of treatment.…”
mentioning
confidence: 99%